Liniowe modele ekonometryczne. Zaawansowane zastosowania języka R - Wdowiński, Piotr (Wydawnictwo Uniwersytetu Łódzkiego, 2026)
This monograph presents advanced applications of the R programming language in econometric analysis, with particular emphasis on linear econometric models. The publication combines theoretical foundations with practical aspects, including algorithm implementation in R, data processing, and automated reporting using R/Markdown. The author discusses stochastic processes, estimation methods, model specification testing, and issues related to assessing models’ fit quality. The book includes numerous R code examples illustrating econometric models, empirical analyses, and forecasting methods for economic and financial variables. A distinctive feature is the integration of econometric techniques with data visualization tools and R/Shiny applications, enabling the development of interactive forecasting systems. The monograph is intended for researchers, data analysts, students of economics and finance, and anyone interested in modern approaches to data analysis in econometrics using R.